If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3) * 2 = 7is Reorder the terms: (3 + x) * 2 = 7is Reorder the terms for easier multiplication: 2(3 + x) = 7is (3 * 2 + x * 2) = 7is (6 + 2x) = 7is Solving 6 + 2x = 7is Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = -6 + 7is Combine like terms: 6 + -6 = 0 0 + 2x = -6 + 7is 2x = -6 + 7is Divide each side by '2'. x = -3 + 3.5is Simplifying x = -3 + 3.5is
| 5ln(-x+2)=49 | | -(7x-7y-6)= | | 3u+5u-5u+-2u=9 | | (X^2/1.47)-x=0.140 | | 2k^2+14k+24=0 | | 2(x+1)+3x=3x+10 | | 2x-69=3x-83 | | -5z-4z-7z-18z=-20 | | 3t^2-11t-4=0 | | (X^2/1.47)-x | | 19=209 | | 14x^2-14x+12=0 | | 6b+7=1 | | 5p-1(-5/6)3p=2 | | 0=-2x^2+4 | | w+1+1w-1= | | 6+6q=10+5q | | 16+11u=9u-18 | | 19-20f=-19f | | -2(y-16)=0 | | 35=.3p | | -5/4(-6/25) | | -8g+12g=-12 | | 4(2+2q)= | | 5=2(n+4)-15 | | 7.37x=.361-2x | | -13=2(n-12)-19 | | 1.5/5=2.1/n | | 2t^2+2(2t)(-1)-1=4t^2+1 | | 14+3t=17t | | -4x^2-16x-3=0 | | m^2+3+19=0 |